The Effect of Social Media on English Language Learning Study in Indonesian Secondary Education - Wulan Nia Umrah; Sukardi Weda; Abdul Halim (International Journal of Language, Education, and Literature, 2025)
Social media has become the most influential media used by society. Social media changes the way people communicate and access information. Although not directly created for educational purposes, social media has attracted the attention of educators, especially in the field of English language learning. Several studies have concluded that social media can be used as a medium in English classes. However, to use social media effectively, it is important to know the influence and effects of social media on students as a reference. Therefore, this study was conducted to explore and determine the effects of social media on Indonesian high school students, the use of social media for English language learning. A total of 30 students from one of the High Schools in North Kolaka were involved in this study. This study uses a qualitative and quantitative approach with a case study design using questionnaires, interviews, and observations as data collection methods. The results showed that students in this study used social media to improve their English. They chose YouTube as the most widely used social media to learn English. Furthermore, some of them also use other social media such as TikTok, Facebook, Instagram. They stated that social media provides a source of English content to practice their English skills, expand their vocabulary and pronunciation. They also stated challenges in using social media for learning, such as internet connection issues, privacy, and inappropriate content. Keywords: Social media, English learning, Indonesian secondary schools, language learning.